2017
DOI: 10.1080/01443615.2016.1264375
|View full text |Cite
|
Sign up to set email alerts
|

PlasmaL-carnitine levels of obese and non-obese polycystic ovary syndrome patients

Abstract: It is well-known that plasma L-carnitine concentrations are significantly decreased in obese individuals. A study showed that L-carnitine concentrations are significantly lower in lean PCOS patients than in lean healthy women. Thus, it has been suggested that lowered L-carnitine is associated with PCOS. This study also showed that the women with PCOS had significantly lower L-carnitine levels than those of the healthy controls. In addition, this study hypothesised that low L-carnitine levels in PCOS patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…However, this elevation is not observed when weight loss is achieved with calorie restriction plus exercise (92). Plasma total L-carnitine level is lower in lean and obese women with polycystic ovary syndrome, a condition frequently associated with insulin resistance, compared to healthy controls (93,94).…”
Section: L-carnitine and Glucose Metabolismmentioning
confidence: 99%
“…However, this elevation is not observed when weight loss is achieved with calorie restriction plus exercise (92). Plasma total L-carnitine level is lower in lean and obese women with polycystic ovary syndrome, a condition frequently associated with insulin resistance, compared to healthy controls (93,94).…”
Section: L-carnitine and Glucose Metabolismmentioning
confidence: 99%
“…Even though no previous study has evaluated TMAO and all its precursors in PCOS, limited data are available on one precursor carnitine suggesting either decreased 23,24 or similar 20 levels in the syndrome compared to healthy women with a wide range of absolute concentrations. On the contrary, we report here higher carnitine levels in PCOS women but the absolute concentrations in both patient and control groups of our study are much lower than those previously reported.…”
Section: Short-term Oc Therapy Combined With Lifestyle Recommendationsmentioning
confidence: 99%
“…These alterations might contribute to increased cardiometabolic risk of PCOS in addition to other proposed mechanisms including hyperandrogenism, anovulation, obesity, insulin resistance, dyslipidemia and subclinical inflammation 1. Accordingly, these preliminary correlation results and their potential implication on cardiometabolic risk in women with PCOS need further exploration.Even though no previous study has evaluated TMAO and all its precursors in PCOS, limited data are available on one precursor carnitine suggesting either decreased23,24 or similar 20 levels in the syndrome compared to healthy women with a wide range of absolute concentrations. On the other hand, TMAO precursor choline showed positive correlation with body fat mass and carnitine showed positive correlations with body fat mass, insulin resistance and triglycerides.…”
mentioning
confidence: 99%
“…Methods that are commonly known to help in ovulation induction in women with PCOS include; weight reduction, lifestyle changes, clomiphene citrate, metformin, gonadotropins, laparoscopic ovarian surgery and In vitro fertilization (IVF) [16] . A study by Celik et al showed that the women with PCOS had a significantly lower L-carnitine levels than those of the healthy controls [9] . Another study reported that L-Carnitine has a significant role in weight loss, glucose tolerance, insulin function and fatty acid metabolism [8] .…”
Section: Discussionmentioning
confidence: 97%
“…L-Carnitine has a significant role in weight loss, glucose tolerance, insulin function and fatty acid metabolism [8] . A study by Celik et al, in 2017 showed that the women with PCOS had significantly lower L-carnitine levels than those of the healthy controls [9] . Another study by Ismail et al, depicted that combined L-carnitine and clomiphene citrate resulted in significant improvement in both ovulation and cumulative pregnancy rates in women with clomiphene-resistant PCOS [10] .…”
Section: Introductionmentioning
confidence: 99%